Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3174/ajnr.a6667
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Subcortical Structures in Youth with Congenital Heart Disease

Abstract: BACKGROUND AND PURPOSE: Congenital heart disease is a leading cause of neurocognitive impairment. Many subcortical structures are known to play a crucial role in higher-order cognitive processing. However, comprehensive anatomic characterization of these structures is currently lacking in the congenital heart disease population. Therefore, this study aimed to compare the morphometry and volume of the globus pallidus, striatum, and thalamus between youth born with congenital heart disease and healthy peers. MAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Indeed, a growing body of quantitative structural MRI studies have reported the presence of regional alterations in brain development in adolescents and young adults with complex CHD [10]. Differences reported include smaller volumes or morphometric variations in the cortical and subcortical grey matter [3,[11][12][13], as well as microstructural alterations predominantly in the association tracts and frontal regions [14,15]. Moreover, previous findings have reported associations between regional structural alterations and cognitive functions; however, these relationships were generally small in magnitude [3,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a growing body of quantitative structural MRI studies have reported the presence of regional alterations in brain development in adolescents and young adults with complex CHD [10]. Differences reported include smaller volumes or morphometric variations in the cortical and subcortical grey matter [3,[11][12][13], as well as microstructural alterations predominantly in the association tracts and frontal regions [14,15]. Moreover, previous findings have reported associations between regional structural alterations and cognitive functions; however, these relationships were generally small in magnitude [3,13,16].…”
Section: Introductionmentioning
confidence: 99%